Poisoning of Dogs by Human Analgesics, Antipyretics and Antiphlogistics - Malinovská Zuzana; Váczi Peter; Čonková Eva (Folia Veterinaria)
Paracetamol, ibuprofen and aspirin are among the most commonly used human analgesics, and antipyretics and ibuprofen and aspirin have antiphlogistic effect. They are found in every household all over the world. People use them every day to treat their pain or fever, and ibuprofen and aspirin to reduce inflammation. Dog owners often use these effective drugs to treat their pets, mostly dogs. They are not aware of their harmful effect on the health of their dogs and have no idea about the risks of poisoning. Intoxication of a dog with these human medicines can end in its death. The article provides a summary of basic information about the clinical symptoms of toxicosis caused by ibuprofen, aspirin and paracetamol in dogs and about their treatment.